Moreno’s bacterial pneumonia score como predictor de neumonía bacteriana en niños con diagnóstico de neumonía en el Hospital Víctor Lazarte Echegaray - Vertiz Barrantes, Edward Andres (2020)
Pneumonia is a frequent infection in the pediatric population, at this stage the most predominant is that acquired in the community, being the predominant viral etiology at younger ages. By not having viral detection tests in all establishments, the etiological diagnosis is difficult to clarify, so age, clinical characteristics, imaging and hematological details are important. Obtaining these data through Moreno's bacterial pneumonia score can predict if the patient presents pneumonia of bacterial etiology and thus establish an antibiotic treatment early and appropriately and also avoid the indiscriminate use of unnecessary antibiotic therapy in patients with etiology viral